2004
DOI: 10.1002/j.1939-4640.2004.tb02847.x
|View full text |Cite
|
Sign up to set email alerts
|

Glu298Asp Endothelial Nitric Oxide Synthase Polymorphism Is a Risk Factor for Erectile Dysfunction in the Mexican Mestizo Population

Abstract: Penile erection depends on the balanced action between antagonist vasoactive molecules such as nitric oxide (NO) and angiotensin. Endothelial nitric oxide synthase (eNOS) and angiotensin-converting enzyme (ACE) polymorphisms have been associated with endothelial dysfunction, which is described as a cause of erectile dysfunction (ED). Endothelial NOS and ACE are both regulators of vascular and corporal smooth muscle tone, which are connected by interaction between the NO-cyclic guanosine monophosphate pathway a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
48
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 37 publications
7
48
0
1
Order By: Relevance
“…For example, Park et al 19 examined 84 Korean patients with organic ED and 63 control subjects of the same age and found significantly higher incidence of the DD genotype in the first group compared to the second (54 and 24% respectively). On the other hand, Rosas-Vargas et al 20 have not found such association in Mexican population.…”
Section: Introductionmentioning
confidence: 82%
“…For example, Park et al 19 examined 84 Korean patients with organic ED and 63 control subjects of the same age and found significantly higher incidence of the DD genotype in the first group compared to the second (54 and 24% respectively). On the other hand, Rosas-Vargas et al 20 have not found such association in Mexican population.…”
Section: Introductionmentioning
confidence: 82%
“…L-arginine is a precursor of NO. Nitric oxide synthases (NOS) are enzymes with an important role in NO production (1,2). Three types of NOS have been described: endothelial NOS (eNOS), neuronal NOS (nNOS) and inducible NOS (iNOS) (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Ho we ver, Kim et al 37 did not de tect any as so ci a ti on bet we en the ACE I/D ge noty pe and ED in the sa me po pu la ti on, com pa tib le with our re sults. Ro sas-Var gas et al 38 al so de ni ed an inf lu en ce of ge noty pes of the ACE I/D poly morp hism on the risk of ED in a Me xi can Mes ti zo po pu la ti on.…”
Section: Discussionmentioning
confidence: 99%
“…In a study from Ger many, Ei sen hardt et al 9 in di ca ted that in di vidu als ho mozy go us for the 894T al le le of the eNOS G894T poly morp hism showed a re du ced res pon se to sil de na fil com pa red with in di vi du als ho mozy gous or he te rozy go us for the 894G al le le. In a Me xi can Mes ti zo po pu la ti on, Ro sas-Var gas et al 38 re por ted that the eNOS 894T al le le was as so ci a ted with an in cre a sed risk for ED. In addition, they sug ges ted that this as so ci a ti on had a prac ti cal imp li ca ti on that might be con si de red in the de ve lop ment of ED therapy pro to cols ba sed on the sti mu la ti on of pe ni le NO synthe sis.…”
Section: Discussionmentioning
confidence: 99%